Direct shear strengthening of NSC and SCC using NSM CFRP and steel bars - Mustafa, Rozhno Omer; Abdul-Kadir, Mohamed Raouf (Sulaimani Journal for Engineering Sciences, 2020)
Failure in direct shear is sudden and catastrophic in concrete structures, Several techniques have been developed for shear strengthening of push-off specimens representing direct shear. In this research, the effectiveness of Near-surface mounted (NSM) FRP and steel bars as a strengthening technique for direct shear in normal strength concrete (NSC) and self-compacted concrete (SCC) are studied. As a result of the experimental work, it was observed that the NSM steel bars increased the shear capacity by 48 and 44% for both types of concrete NSC and SCC respectively, while the NSM CFRP rods increased the shear capacity by 30% and 33% for both NSC and SCC respectively. It was also observed that strengthening at 90° was more effective in terms of shear strength compared to 45° with a difference in the range of 8% for NSC and 5% for SCC. The analytical results are very close to the experimental ones.
Keywords: Direct shear; NSM; Strengthening; CFRP rod